MAKNA SIMBOL BUSANA TARI BENTABUH SUKU DAYAK JAWATN DI DESA MONDI KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Kusumayanti, Regina; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstrakBackground of this study was about the existency of symbol meaning that needs to be described related to the clothes that are used in Bentabuh dance. The research design of this study was Descriptive Analysis that was presented informs of qualitative research and fenomenology approach. The technique of the data validation test was presented informs of extensive observation, triangulation source, and triangulation technique. The result of this study ere presented informs of the clothes that is used by the dancers based on the on their characters such as Penongah (a guardian), a bride and groom, their KombarÂ (a bridesmaid and groomsman) and two other dancers whose characters are as to hold a chicken and yellow rice.The meaning of the symbol of dance clothing Bentabuh can be seen from the stripes on the clothes (standing dragon is described as the symbol of the strength,Â and also bamboo shoots, flowers, ferns, and leaves that symbolize that their life is depending on the nature), shapes (depending on the user's gender), colours (black, white, yellow, red, and gold). In addition, the result of this study are expected to be implemented in the course of Seni Budaya for eleventh (XI) graders. Keywords: Bentabuh, Dance Clothes, Symbol Meaning.